PENGARUH LEVERAGE DAN PROFITABILITAS TERHADAP KUALITAS LABA YANG TERDAPAT PADA PERUSAHAAN INDEKS LQ45 YANG TERDAFTAR DI BURSA EFEK INDONESIA - Novia Suci Ramadhani; Mike Kusuma Dewi (LPPM Universitas Bina Bangsa, 2024)
This research aims to test whether there is an regression of leverage and profitability on earnings quality in LQ45 index companies listed on the Indonesian Stock Exchange for the 2019-2022 period. In this research, the object taken is the LQ45 Index Company which is listed on the Indonesia Stock Exchange (BEI). The type of data used in this research is panel data. The measurement scale used in this research by the author is the ratio scale. The data source in this research is secondary data, by obtaining data indirectly from books, financial reports which can be accessed via the Indonesian Stock Exchange authority website (www.idx.co.id), and other sites related to check the required data. In this research, the population that is the object of research is a total of 45 companies on the LQ45 Index listed on the Indonesian Securities Exchange for the 2019-2022 period. The sample method used in this research was determined based on the porposive sampling method, with predetermined criteria, companies that were consistently found in the LQ45 Index companies listed on the Indonesia Stock Exchange. The data collection technique used by researchers in this research is the documentation technique. The results of the leverage research have no effect on the quality of earnings in LQ45 Index companies listed on the Indonesia Stock Exchange (BEI) for the 2019-2022 period and profitability has a negative effect on the quality of earnings for LQ45 Index companies listed on the Indonesia Stock Exchange (BEI) for the 2019-2022 period